Improving LAN Performance Based on IEEE802.1Q VLAN Switching Techniques (Journal of University of Babylon for Engineering Sciences, 2017)
VLAN is a set of users in different isolated logical LANs or broadcasting domains, they are communicated as a same LAN i.e. same broadcasting domain. Ethernet protocol is very popular over networks because it has a simple of implementation and ease of configuration. However, the support of Quality of Service (QoS) has become an essential merit of Ethernet network. In this context, the problems of large network and data transport delay have been regained significant importance. Alleviating the end to end delay by using the VLAN technology to enhance the network performance. In this paper, we analyze and evaluate the performance of LAN and VLAN networks in different scenarios. Measuring key performance indicators such as traffic sent, traffic received, average delay and throughput. The simulation was carried out by employing OPNET 17.5 Student Version. Two different scenarios are presented to observe the performance of LAN and VLAN networks. The simulation results illustrated that there is more existing traffic without VLAN technology. Hence, VLANs prohibit the access to the network resources of other departments. Also, VLAN has half average queuing delay compared with no VLAN scenario. Therefore, VLANs can improve bandwidth utilization, power, speed and security.